Social interactions of migrants and trade outcomes - Silvio Hong Tiing Tai (World Trade Organization (WTO), 2009)
A framework for immigrant's choice of location is based on recent studies on non-market interactions which explains how migrants concentrate. Applying data on the distribution of immigrants in 95 French provinces, the social interactions are subsequently estimated. This "social component" of migration is then tested on international trade, providing a direct measure of the impact of social networks on the economy.
Keywords: F10; F22; 330; Social interaction; non-market interaction; international Trade; migration; Soziale Beziehungen; Migranten; Außenwirtschaft; Frankreich